Challenges during the transition from child and adolescent mental health services to adult mental health services. (August 2020) - Hendrickx, Gaelle; De Roeck, Veronique; Maras, Athanasios; Dieleman, Gwen; Gerritsen, Suzanne; Purper-Ouakil, Diane; Russet, Frédérick; Schepker, Renate; Signorini, Giulia; Singh, Swaran Preet; Street, Cathy; Tuomainen, Helena; et al.
Abstract : The transition from child and adolescent to adult mental health services for young people with mental health problems is of international concern. Despite the high prevalence of mental disorders during adolescence and their tendency to continue during adulthood, the majority of young people do not experience continuity of care. The aim of this review paper is to unravel the complexity of transitional mental healthcare to clinicians, policy makers and mental health service managers, and to address challenges to a smooth transition process at all levels.